Generic synopsis of the jumping plant-lice (Hemiptera: Sternorrhyncha: Psylloidea) from Colombia - Rendón-Mera, Diana Isabel; Serna, Francisco; Burckhardt, Daniel (Zootaxa, 2017)
Jumping plant-lice (Hemiptera: Sternorrhyncha: Psylloidea) are a group of phloem-feeding insects with nearly 4000        described species. Previous records from Colombia comprise 19 genera of all eight known families. The revision of material deposited in six Colombian and three foreign museums yielded another nine genera that constitute new country records. Material from 16 departments was examined. Each genus is diagnosed and information is provided on biology, damage and host-plants. Local distribution maps and a generic key for the identification of adults are provided.